Amplatzer amulet versus watchman device for percutaneous left atrial appendage closure: a systematic review and meta-analysis. (25th January 2023) - Jaiswal, V I K A S H; Ang, S O N G P; Shrestha, A B; Sharma, P R A C H I; Endurance, E O; Khan, S H A Z I A; Mukherjee, D; Jaiswal, A K A S H; Chia, J I A E E; Huang, H E L E N; Alraies, M C; Biswas, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The Amplatzer Amulet and Watchman devices are the two most frequently used devices for percutaneous LAA closure globally. Aim: To evaluate the safety and clinical outcomes associated with these two devices in patients undergoing percutaneous LAA closure. Method: A systematic literature search was performed in PubMed, Scopus, Embase, and Cochrane databases for studies comparing the safety and outcomes of patients undergoing LAA closure using either Amulet or Watchman devices. The primary outcome was all-cause mortality. Secondary outcomes were incidence of ischemic stroke, systemic/pulmonary embolism, major bleeding, and procedure-related complications. Results: A total of 3 randomized clinical trials with 2150 patients were included in this meta-analysis. The mean age was 75 years and 76 years in the Amplatzer group and in the Watchman group, respectively. The mean CHA2DS2-VASc score (4.2 vs. 4.34) and mean HAS-BLED score (3.46 vs. 3.56) were comparable between both groups. The odds of all-cause mortality (OR, 0.74 (95% CI: 0.48-1.13), p = 0.16), ischemic stroke (OR, 0.81 (95% CI: 0.27-2.49), p = 0.72), systemic/pulmonary embolism (OR, 1.33 (95% CI: 0.29-6.00), p = 0.71), and major bleeding (OR, 1.10 (95%CI: 0.82-1.48), p = 0.51) were comparable between the two devices. In contrast, procedure-related complications (OR, 2.11 (95%CI: 1.31-3.40), p = 0.002) were significantly higher among patients with Amplatzer Amulet compared to the Watchman device. Conclusion: The Amplatzer Amulet was non-inferior to the Watchman device in terms of safety and efficacy. However, the Amulet occluder was associated with a higher incidence of procedure-related complications. Graphical illustration Forest Plot